Evidence-Based Research on Barriers and Physical Limitations in Hospital Public Zones Regarding the Universal Design Approach - Charanya Phaholthep; Antika Sawadsri; Thirawut Bunyasakseri (My University, 2017)
The hospital is a public building which has the primary duty to provide services to everyone. So far, it is necessary to take into consideration the principle of Universal Design (UD) in responding to the behavior of users, particularly, persons with disabilities. This research focused on 2 main issues, (1) the physical features of the public areas for measurement and collection regarding to the style, size and location of facilities, and whether they meet the requirement and/or appropriate for people with disabilities, and (2) behavior of users with disabilities in accessing spaces and service facilities in the hospital public zones, focusing on the involvement between activities, behaviors and problems which occur. This research used empirical method to assess and evaluate the physical features by the process of Post Occupancy Evaluation, (POE), using 2 evaluation methods, 1) survey/observation (Cognitive walkthrough) and 2) scenario access audit methods. In detail, the survey/observation focused on the obstacles within a physical environment that affect space and service activities regarding people with different types of disabilities. Identifying the obstructions in public functions and health care facilities was implemented by a group of design specialists. On the other hand, the scenario access audit process was operated by determining the level of accessibility and the real patient flow of patients with disabilities on-sites and spaces in public zones. Therefore, this research speculated on all problems and came up with the design guidelines to improve the physical features of public zones in responding to the usability of the service facilities under the UD approach.
Keywords: Post-occupancy evaluation; Cognitive walkthrough; Geriatric Care and Nursing Homes